Study for Gamma Ray Spectra of Cascading Decay - Jassim, Fatima (Iraqi Journal of Science, 2025)
Relative intensity to the single peaks and true sum peaks to the elements of cascading decay of gamma-rays as Co and "y have been measured for different point source detector distances by using 33 Nal(Tl) detector into two different methods. These methods give a good information to distinguish between single and true sum peaks especially in analysis a complex puise height spectrum; where the relative intensity for true sum peak varies with source detector distance while it is independent for single peak. The results of two the methods are in fair agreement.